Creative advertising concept and copy : a practical, multidisciplinary approach - Miliopoulou, Georgia-Zozeta (Routledge, 2024)
"Considering perspectives on creative advertising through a unique media and communications lens, this book encompasses both the theory and practical tools needed to approach and understand creativity in advertising with an original eye. Drawing from diverse subject areas including Social Anthropology, Narrative Theory, Consumer Psychology, Semiotics and Cultural Studies, Creative Advertising provides a solid grounding in advertising education away from the traditional business and marketing literature. Notwithstanding the need for independent inspiration and originality, the author guides readers through the entire process of campaign planning, moving from strategy to creative idea to finished piece whilst employing concepts and principles relevant to 'design thinking'. Taking into account ethics and regulations, the use of text and images, and storytelling across radio, TV and video platforms, readers will come to a holistic understanding of what advertising can (and cannot) do, and how to achieve the best results. Written for students involved in creative advertising as an area of academic research and professional practice, this book will also be of interest to early-career advertising professionals seeking a fresh perspective on their work"-- Provided by publisher.